Correlation Between Y-Balance Test and Balance, Functional Performance, and Outcome Measures in Patients Following ACL Reconstruction - Jin Seong Kim; Ui Jae Hwang; Moon Young Choi; Doo Hwan Kong; Kyu Sung Chung; Jeong Ku Ha; Oh Yun Kwon (International Journal of Sports Physical Therapy)
# Background